Macrophytes and periphyton carbon subsidies to bacterioplankton and zooplankton in a shallow eutrophic lake in tropical China. (31st January 2015) - de Kluijver, A.; Ning, J.; Liu, Z.; Jeppesen, E.; Gulati, R. D.; Middelburg, J. J.
Abstract The subsidy of carbon derived from macrophytes and associated periphyton to bacterioplankton and zooplankton in subtropical shallow eutrophic Huizhou West Lake in China was analyzed using carbon stable isotope signatures. A restored part of the lake dominated by macrophytes was compared with an unrestored phytoplankton‐dominated part. Macrophytes, periphyton, seston, and zooplankton were sampled every two months to determine natural‐abundance carbon isotope ratios (δ13C). The δ13C of phytoplankton and bacterioplankton was determined from δ13C of fatty acid biomarkers. Macrophytes and associated periphyton had similar δ13C values and were the most enriched in 13C of all measured organic carbon pools. A macrophyte–periphyton carbon isotopic signal was detected in particulate organic carbon, bacterioplankton, and zooplankton in the macrophyte‐dominated lake part, which was demonstrated by a significant enrichment in 13C compared with the unrestored part, while phytoplankton and dissolved organic carbon had similar δ13C values in both lake parts. A two‐source (macrophytes–periphyton and phytoplankton) mixing model showed that macrophytes–periphyton potentially contributed 14–85% (average 55%) to bacterioplankton in the macrophyte‐dominated lake part, depending on season. The macrophytes–periphyton contribution to zooplankton seasonally varied between 26% and 86%, with an average of 47%. The contribution of macrophytes–periphyton to bacterioplankton increased with increasing macrophyte biomass relative to phytoplankton biomass (indicated by chlorophyll a). Carbon from macrophytes with associated periphyton subsidizes bacterioplankton and zooplankton, likely enhancing the cascading effects of planktonic food webs, providing an additional explanation for the stability of a clear‐water state in shallow lakes dominated by macrophytes.